2023
DOI: 10.1073/pnas.2307638120
|View full text |Cite
|
Sign up to set email alerts
|

Widespread use of proton-pumping rhodopsin in Antarctic phytoplankton

Sarah M. Andrew,
Carly M. Moreno,
Kaylie Plumb
et al.

Abstract: Photosynthetic carbon (C) fixation by phytoplankton in the Southern Ocean (SO) plays a critical role in regulating air–sea exchange of carbon dioxide and thus global climate. In the SO, photosynthesis (PS) is often constrained by low iron, low temperatures, and low but highly variable light intensities. Recently, proton-pumping rhodopsins (PPRs) were identified in marine phytoplankton, providing an alternate iron-free, light-driven source of cellular energy. These proteins pump protons across cellular membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…These results are consistent with previous studies that have also observed increased ISIPs and RHO expression in diatoms to cope with Fe stress (Cohen et al 2017; Behnke and LaRoche 2020). The significantly increased expression of RHO with respect to the DFB treatment could suggest the potential usage of an Fe‐independent energy production/conservation strategy by diatoms under Fe limiting conditions (Marchetti et al 2015; Andrew et al 2023; Strauss et al 2023). Although DFB is not necessarily a quantitative predictor of future Fe limitation, it does present a scenario of how declining Fe bioavailability can influence diatom physiology and gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies that have also observed increased ISIPs and RHO expression in diatoms to cope with Fe stress (Cohen et al 2017; Behnke and LaRoche 2020). The significantly increased expression of RHO with respect to the DFB treatment could suggest the potential usage of an Fe‐independent energy production/conservation strategy by diatoms under Fe limiting conditions (Marchetti et al 2015; Andrew et al 2023; Strauss et al 2023). Although DFB is not necessarily a quantitative predictor of future Fe limitation, it does present a scenario of how declining Fe bioavailability can influence diatom physiology and gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Gains and losses of species in response to the ongoing changes in Arctic habitats (e.g., decrease in sea ice coverage and increased seawater temperature) are likely to induce significant food web reorganization with potential cascade effects (Beaugrand et al 2019; Kortsch et al 2015). Microbial eukaryotes differ in their thermal tolerance (Demory et al 2019), dispersal capacity (Villarino et al 2018) and ability to exploit new resources, (Andrew et al 2023) which contributes to their abundance and diversity patterns. Therefore, they are natural proxies of community turnover and ecosystem shifts.…”
Section: Introductionmentioning
confidence: 99%
“…These membrane proteins contain the embedded pigment retinal, and upon absorption of light, the pigment–protein complex transports a hydrogen ion across the cellular membrane in which the PPR is embedded. The resultant membrane pH gradient can then be used to drive active membrane transport of essential nutrients and biomolecules and to synthesize adenosine triphosphate (ATP), the energy currency of the cell [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments with the marine diatom Pseudo-nitzschia subcurvata isolated from the cold, iron-poor waters of the Southern Ocean (SO) have shown that PPR is localized in the vacuolar membrane of this species [ 7 ]. Experiments with this and two other SO diatoms ( Chaetoceros sociales and Synedra hyperborea ) showed that cellular PPR levels increased in low-iron cultures [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation